Implementation of Viet Nam's population strategy: 2001 - 2005 : (Nhà xuất bản Hà Nội, 2006)
The purpose was to assess the execution of the strategy, and to document lessons learned and experiences drawn from its dilivery. Fiding and recommendations of the review were intended to serve as evidence for the VCPFC to decide in directions for deploying the population strategy for the period 2006-2010.